تكامل مفهوم المحبة بين الطبيعة والتصوف والوحي عند ابن تيمية - Nur Hadi Ihsan; Asif Trisnani; Muhamad Syifaurrahman (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2021)
AbstractThere are so many studies discuss mahabbah according to prominent Sufi figures. This study will elaborate on the concept of mahabbah from the perspective of nature, Sufism, and revelation in the view of Ibn Taimiyah, a prominent Muslim thinker who is known to be a very critical of the teachings and practices in Sufism. This paper is a library research utilizing a Sufism approach. The data in this work were obtained using documentary techniques by referring to the main work of Ibn Taimiyah, namely Qa'idah fi al-Mahabbah. The collected data were analyzed employing descriptive-analysis method. This paper finds that Ibn Taimiyya used different terms from the Sufis to describe the highest level of mahabbah. For most Sufis, the highest level of mahabbah is expressed by the term ishq. As for Ibn Taimiyya, the word ishq is a form and level of excessive love and is therefore considered corrupted. Instead of ishq, Ibn Taimiyya preferred the term khullah. Like the Sufis, Ibn Taimiyya also stated that everything that happens in this world is because of mahabbah of Allah. Then, according to Ibn Taimiyah, mahabbah is closely related to worship, because worship is a form of perfect love of the servant to his Creator. Mahabbah also has a close relationship with ma'rifatullah, because by knowing  God; knowing His names and His attributes will lead to perfect worship and perfect love (mahabbah).ملخص البحثكثرت البحوث والدراسات التي تناقش المحبة في أفكار الصوفية البارزين. وستتناول هذه الدراسة بالكشف عن مفهوم المحبة بمنظور علم الطبيعة والتصوف والوحي عند ابن تيمية، المفكر المسلم البارز المعروف بالنقد القوي لتعاليم وممارسات التصوف. هذه المقالة عبارة عن دراسة مكتبية باستخدام الدراسة الصوفية. وأخذت بيانات هذه الدراسة من التقنيات الوثائقية بالرجوع إلى العمل الرئيسي لابن تيمية، وهو "القاعدة في المحبة". ثم تم تحليل البيانات المجمعة باستخدام منهج التحليل الوصفي. وبعد البحث والتحليل وجد الباحثون أن ابن تيمية استخدم مصطلح مختلف عن الصوفية لوصف أعلى مستوى المحبة. بالنسبة لمعظم الصوفيين فإنه يتم التعبير عن أعلى مستوى المحبة بمصطلح "عشق". أما ابن تيمية فإنه يرى أن كلمة "ِعشق" هي درجة من الحب المفرط الذي يؤدي إلى المفهوم المخطئ. بدلا من عشق ، فضل ابن تيمية مصطلح "الخلّة". ثم ذكر ابن تيمية أن كل ما يحدث في هذا الكون يرجع إلى فضل الله و محبته. ثم ذهب بأن المحبة ترتبط ارتباطًا وثيقًا بالعبادة ، لأن العبادة هي شكل من أشكال الحب الكامل للخالق. كما أن المحبة لها علاقة وثيقة بمعرفة الله. لأنها بمعرفة الله: معرفة أسمائه وصفاته ستؤدي إلى عبادة كاملة ومحبة تامة.